Implementasi Augmented Reality dalam Pencarian Buku Referensi Mata Kuliah TI di Perpustakaan Universitas Dhyana Pura Menggunakan Metode Marker Based Tracking - Ni Putu Ria Anggreni; Feoh, Gerson; Prastyadi Wibawa Rahayu; I Nyoman Bernadus (STEKOM PRESS, 2024)
The background of this research is the lack of interest of Dhyana Pura University Informatics Engineering Study Program students in visiting the library. This shows the need for a new innovation in the library that can increase the attractiveness of students to visit the library more often. The purpose of this study was to implement augmented reality with the Android-based marker-based tracking method in the search system for reference books for IT courses in the UNDHIRA library, to find out the results of the analysis of the level of user convenience and satisfaction in using the application, as well as to find out the results of a comparison of the level of interest in student visits to the library before and after system implementation. This research is a quantitative study; the data was collected using a questionnaire technique on 54 application users. The results showed that the usability of the application was 87.41% or could be classified as